Beyond Criminal Law: Repositioning Administrative Law as the Primary Instrument of Anti-Corruption Enforcement in Indonesia - Ade Kosasih; Iskandar; Yamani M; Muslih Ahmad; Rami Putri Redani (YURIS: Journal of Court and Justice, 2026)
Corruption in public administration is largely rooted in the abuse of authority by public officials in exercising governmental powers. In Indonesia, anti-corruption strategies have predominantly relied on criminal law enforcement, which tends to address corruption only at the symptomatic level rather than tackling its structural causes. This study argues that administrative law should function as a primary instrument (primum remedium) in combating corruption, given its central role in regulating the exercise of public authority and ensuring accountability in governance. This research employs a normative juridical method with an explanatory approach, using statutory, conceptual, and doctrinal analyses of legal materials derived from legislation, court decisions, and international anti-corruption instruments. The findings indicate that the limited effectiveness of corruption eradication in Indonesia is closely related to weak preventive administrative mechanisms, non-independent internal supervision, and ineffective enforcement of administrative sanctions against abuse of power. Strengthening administrative law enforcement through preventive, repressive, and restorative mechanisms can significantly enhance anti-corruption governance. Key reforms include merit-based recruitment of public officials, independent administrative oversight, stricter monitoring of officials’ assets, digitalization of public services, and the firm application of administrative sanctions without waiting for criminal conviction. These measures can improve institutional accountability and strengthen good governance as a structural strategy to prevent corruption.